L'héritage de l'esclavage : éléments pour une autre approche de la condition de femme - Davis, Angela (Femmes, race et classe, 2007)
Première publication: 1983
Keywords: afro-féminisme; amériques; approches et analyses; classe sociale; cours; fem1000; féminismes noirs; histoire et politique; inégalités; militance; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Le viol, le racisme et le mythe du violeur noir - Davis, Angela (Femmes, race et classe, 2007)
Première publication 1981
Keywords: afro-féminisme; amériques; approches et analyses; cours; fem1000; féminismes noirs; inégalités; militance; premier cycle; racisme; régions géographiques; stéréotypes; systèmes d'oppressions; thématiques; travail; violences; états-unis

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences